Penggunaan magic dalam politik lokal di Banten - Ayatullah Humaeni (Faculty of Social and Political Science, Universitas Airlangga, 2014)
Village-head elections frequently become unhealthy competitions among the candidate. They employ various ways to win the election, including using magical means. This article aims to explain social phenomena occur in local politics in the use of magic village-head elections in rural Banten; particularly in two sub-districts, Ciomas and Padarincang. It tries to answer several main research questions: (1) why do the candidates make use of magic during the village election process?; (2) what kinds of magic used by the candidates; (3) How does magic influence the winning chance of village head elections? (4) and how is the process of the magic usage during the village election process?. This article is the result of a field research using ethnographical method based on anthropological perspective. To analyze the data, the researcher uses structural-functional approach. Library research, participant-observation, and depth-interview are methods used to collect the data. Based on the result of field research, it can be concluded that almost all of the candidates in these two sub-districts made use of magic in order to win the village head elections. They visit several magicians and made use of their super natural powers for their own purposes. They believed that magical power possessed by these magicians could influence their winning chance in the village-head elections. Various fundamental reasons also become an important consideration why the candidates need to use magic in local politics process.